Husserl and the “Shrapnel” of War: Origins of Reflections on the Crisis of European Culture (Phenomenology, Humanities and Sciences, 2023)
The hypothesis formulated by this paper consists of showing that the phenomenon of the first world war was decisive in the direction of edmund husserl’s itinerary in the 20th century. based on this phenomenon and the impacts it had on husserl’s personal life, one can notice the author’s growing interest in reflections in the field of culture, forcing him to develop his first considerations on the theme of the crisis of european man. the article has two parts: the first is dedicated to the context of the war and its impacts on husserl’s thought, while the second focuses on the famous “lessons on fichte”, taught by the author in 1917-1918, still under the shrapnel and noises produced by the war.
Keywords: Edmund Husserl; First World War; Europe; Crisis; Humanity